THE INFLUENCE OF DIGITAL LITERACY, FINANCIAL LITERACY, GENDER, AND FEAR OF MISSING OUT (FOMO) ON STOCK INVESTMENT DECISIONS WITH INFORMATION DISCLOSURE AS A MEDIATING VARIABLE AMONG GENERATIONS Y AND Z IN WEST JAVA - Rina Herlina; Erna Puji Hartanti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of the digital economy has encouraged an increasing number of Generation Z students to pursue higher education while simultaneously engaging in side hustles. This condition requires students to manage role balance and maintain motivation to ensure that both academic and work-related activities lead to satisfactory outcomes. Role imbalance and low motivation may reduce students’ satisfaction and overall well-being, making this issue important to examine. This study aims to analyze the effect of Work-Life Balance and Motivation on Activity Satisfaction among Generation Z students engaged in side hustles at Universitas Wanita Internasional. A quantitative approach with an associative research design was employed. Data were collected through questionnaires distributed to 126 respondents selected using purposive sampling. The data were analyzed using multiple linear regression supported by t-tests, F-tests, and the coefficient of determination. The results indicate that Work-Life Balance and Motivation have a positive and significant effect on Activity Satisfaction, both partially and simultaneously. Motivation was found to have a more dominant influence compared to Work-Life Balance. These findings support the Self-Determination Theory and provide practical implications for managing student activities. Future research is recommended to incorporate additional psychological and contextual variables.